The scientific and practical aspects of exercise metabolism - Morris, Alfred F.; Monterey Bay Video Production Company (Monterey, CA : Monterey Bay Video Production Company, 2007)
Presents a detailed review of the four factors that determine whether an individual burns fat or carbohydrate when exercising. In an easy-to-understand, straightforward manner, the video addresses the issues of when, how, and why individuals utilize fat or carbohydrates when exercising
Keywords: Metabolism; Exercise -- Physiological aspects; Physical fitness -- Physiological aspects